Water erosion and the vulnerability of ecological balances; The case of the lower part of Oued Za basin (Eastern Morocco) - BENHAMED, Abderrahim; SBAI, Abdelkader (Journal of natural sciences, life and applied sciences, 2024)
The Oujda-Taza corridor has witnessed spatial transformations, It has led to problems that threaten the preservation and sustainability of natural resources, One of the most important reasons for these transformations is the problem of water erosion, which is considered an inevitable result of climate change and the extreme natural phenomena it produces. (drought, opening of vegetation cover, concentration of precipitation in time and place), Which led to land degradation in the lower part of the Oued Za basin, exacerbated by human pressure and the accompanying shifts in exploitation patterns that led to the activation and acceleration of morphodynamic processes, creating a group of environmental, economic and social problems (soil loss, dam muddying, population migration). This study aims to know the characteristics of the environment and identify the various factors responsible for the risk of water erosion, and assess the extent of this risk by analyzing the available data, carrying out direct measurements in the field by exploiting the rain simulator, and estimating the amount of soil lost through the Universal Equation for Estimating Lost Soil (USEL). After calculating various factors, it was found that 7% of the basin area is subject to strong erosion, and the average amount of soil lost is estimated at 5.2 tons/ha/year, while direct measurements showed clear differences in the hydrological response and amounts of lost soil as a function of the difference in natural characteristics. (Nature of the soil, degree of slope of the slopes, orientation...) and exploitation patterns (rested land, plowed, direction of plowing...). The amount of removed soil ranged between 0.12 tons/ha for plots with vegetation, and 3.23 tons/ha for bare lands with strong slopes.